Sensitivity of field tests for assessment of wrestlers specific fitness - Markovic, M.; Toskic, L.; Kukic, F.; Zaric, I.; Dopsaj, M. (Journal of Human Kinetics, 2022)
The aim of this study was to determine the differences in performance, cardiac, and metabolic variables of combat-specific fitness of wrestlers from varying sports levels. The sample consisted of 61 active and highly trained adult wrestlers of national and international levels from Serbia, from both Greco-Roman and freestyle forms of wrestling, allocated into three groups: national team wrestlers (N = 15), first league competitive wrestlers (N = 20), and second league competitive wrestlers (N = 26). Participants performed two tests: a Specific Wrestling Fitness Test (SWFT) and a Specific Wrestling Performance Test (SWPT). Between-group differences were determined using multiple analysis of variance (MANOVA). Significant differences were obtained between wrestlers of different sports levels in Tn Throws (F = 77.491, p < 0.001), SJFIndex (F = 49.710, p < 0.001), and SWPIndex (F = 31.205, p < 0.001) in the SWFT and in TnThrows (F = 71.051, p < 0.001), SJF Index F = 45.343, p < 0.001), and SWPIndex (F = 26.820, p < 0.001) in the SWPT. Based on the results, it could be concluded that the SWFT and the SWPT provide very good sensitivity in the evaluation of the wrestlers specific fitness of wrestlers.